Pengaruh Lingkungan Kerja, Kompensasi dan Semangat Kerja Terhadap Kinerja Driver di Wilayah Palembang - Halima Eka Diansari; Juhaini Alie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of the work environment, compensation and work morale on the performance of Gojek drivers in the Palembang area. The research design used in this research uses an associative method. The analytical methods used are quantitative and qualitative methods. The variables used are 3 independent variables, namely motivation, work discipline and work environment and the dependent variable is employee performance. The research data sample used in the research was 100. The analytical tools used were the classical assumption model test, multiple linear regression analysis, coefficient of determination, F test and t test. The research results show that simultaneously the variables of work environment, compensation and work morale influence the performance of Gojek drivers in the Palembang area. Partially, it shows that the work environment has an influence on the performance of Gojek drivers. Compensation affects the performance of Gojek drivers. Work enthusiasm influences the performance of Gojek drivers in the Palembang area.